2022
DOI: 10.1186/s12911-022-01906-6
|View full text |Cite
|
Sign up to set email alerts
|

Supporting family care: a scoping app review

Abstract: Background Mobile applications (apps) may provide family caregivers of people with chronic diseases and conditions with access to support and good information. However, thorough understanding of how these apps meet the main needs and requirements of the users is currently lacking. The aim of this study was to review the currently available apps for family caregivers and evaluate their relevance to main domains of caregiving activities, caregivers’ personal needs, and caregivers’ groups found in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…The studies identified by the search strategy have been selected based on whether they met all of the inclusion criteria outlined as follows: 1) Caregivers were informal carers or unpaid voluntary helpers; 2) The article describes or evaluates an AI-based technology or assistive technology developed with the primary or secondary goal to assist informal carers in fulfilling their caregiving duties and personal needs, mentioned in the referenced literature (i.e. [21]). On the contrary, articles were not included whether they met any of the following exclusion criteria: 1) targeted caregivers were professionals; 2) the AI-based technology or assistive technology was not expressively tailor-made for caregiving; 3) articles were not in English; 4) articles were reviews, commentaries, abstract, theoretical frameworks.…”
Section: Acmmentioning
confidence: 99%
“…The studies identified by the search strategy have been selected based on whether they met all of the inclusion criteria outlined as follows: 1) Caregivers were informal carers or unpaid voluntary helpers; 2) The article describes or evaluates an AI-based technology or assistive technology developed with the primary or secondary goal to assist informal carers in fulfilling their caregiving duties and personal needs, mentioned in the referenced literature (i.e. [21]). On the contrary, articles were not included whether they met any of the following exclusion criteria: 1) targeted caregivers were professionals; 2) the AI-based technology or assistive technology was not expressively tailor-made for caregiving; 3) articles were not in English; 4) articles were reviews, commentaries, abstract, theoretical frameworks.…”
Section: Acmmentioning
confidence: 99%
“…Zahlreiche Anbieter digitaler Angebote haben es sich zur Aufgabe gemacht, Lösungen für diese Informations- und Koordinationsbedarfe zu entwickeln [ 1 , 18 ]. Auch politische Akteure setzen große Hoffnungen in digitale Anwendungen und fördern diese durch die Schaffung rechtlicher Rahmenbedingungen, etwa für digitale Pflegeanwendungen (DiPA).…”
Section: Hintergrund Und Studienzielunclassified
“…However, it is important to note that not all IT applications effectively support informal caregivers. A previous scoping review found that IT applications focus more on supporting caregivers in their caregiving role than their private and professional life [13]. Therefore, it is important to identify IT applications that cater to the primary caregiving and personal need domains of informal caregivers.…”
Section: Overviewmentioning
confidence: 99%